The Effect of Vendor Trustworthiness toward Online Purchase Intention through Costumer Trust - Adiwijaya, Michael (International Research Journal of Business Studies, 2014)
The using of internet technology in business field facilitates the online product sales. There are many challenges and obstacles faced by customers when they would like to buy product via online, for instance the process of technology adoption, online crime activities, etc. This situation creates customer doubtfullness and worries for engaging in purchasing product via online. Trust plays significant role in affecting customer intention to purchase products via online. The previous research findings showed the antecedents of customer trust but those findings only explained the phenomenon based on one single perspective for example from the customer perspective, the technology perspective, and the vendor perspective. The focus of this research is analyzing the influence of vendor trustworthiness (ability, benevolence, and integrity) towards individual features (customer trust) and customer purchase intention. The research has been done in Surabaya through questionairre survey design by using the customers who had purchase product via online as the respondent. Structural equation modelling is used to analyze the research data. The findings revealed the antecendent of customer trust and its influence on customer online purchase intention comprehensively.